The Study of Performance Art Ã¢â‚¬Å“Kethuk RosoÃ¢â‚¬Â by Fenny Rochbeind - Pristiati, Tutut; Sunarto, Sunarto; Wadiyo, Wadiyo (Catharsis, 2018)
Performance artÃ¢â‚¬ÂKethuk RosoÃ¢â‚¬Â is a form of spontaneity of body action as a media of expression that presents the stretching of the spirituality of the artist to knock the sense of audience to interpret the morality. This study aims to describe the visual form and characteristics of performance Ã¢â‚¬Å“Kethuk RosoÃ¢â‚¬Â by Fenny Rochbeind. This research used qualitative method with interdisciplinary approach. The source of the data used primary and secondary data through observation, interview, and documentary techniques. The validaty data technique used source of triangulation and the analysis technique data is done with performance art theory by RoseLee Goldberg. The result shows that performance art of Ã¢â‚¬Å“Kethuk RosoÃ¢â‚¬Â is a multidisciplinary in the form of non-profit art genre that primarily focuses on the body as a media expression that directly conveys a dialogical message between the performer and the audience in the form of action communication. The researcher expects that through appreciation of performance art Ã¢â‚¬Å“Kethuk RosoÃ¢â‚¬Â is important to be known by the public especially for art educators to understand, appreciate, and apply the contemporary art form which gives new color and meaning in art and to support the development of basic competence in art education. The research findings that Kethuk Roso performance art is able to knock everybody's sense of responding to cases of physical violence. Performance art Kethuk Roso proves its manifestation as a contemporary art shows the actual and factual events which gives new colors and meaning.